Bibliometric analysis of scientific production in futsal - Palazón, M. A.; Ortega, E.; García-Angulo, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2015)
The aim of this study is to conduct an analysis of the scientific production in the sport of futsal. To do this the main collection platform “Web of Science” with databases Science Citation Index Expanded (SCI-EXPANDED) and Social Sciences Citation Index (SSCI) was used. The search provided 81 articles of which the following variables were analyzed: 1) title; 2) name of the first author; 3) institution of the first author; 4) number of authors; 5) magazine; 6) number of citations; 7) year of publication; 8) main discipline of study; 9) type of study; 10) sample size; 11) sport level of the sample, 12) sex shows. The results highlighted the experimental items, the male and a professional level. Concerning institutions, highlights countries with booming in regards to football, as Brazil and Portugal.